2020
DOI: 10.1038/s41567-020-0993-7
|View full text |Cite|
|
Sign up to set email alerts
|

Spectroscopic fingerprint of charge order melting driven by quantum fluctuations in a cuprate

Abstract: Copper oxide high-T C superconductors possess a number of exotic orders that coexist with or are proximal to superconductivity. Quantum fluctuations associated with these orders may account for the unusual characteristics of the normal state, and possibly affect the superconductivity 1-4 . Yet, spectroscopic evidence for such quantum fluctuations remains elusive. Here, we use resonant inelastic X-ray scattering to reveal spectroscopic evidence of fluctuations associated with a charge order 5-14 in nearly optim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 39 publications
(93 reference statements)
7
54
0
Order By: Relevance
“…Phase excitations of stripes couple to the lattice and create a splitting of the in-phase and out-of-phase oscillation modes (35). However, the phonon anomaly is expected (35) to exist within a narrow (17,19,20). This is supported by a nonmonotonically increasing phonon intensity versus momentum and an excitation energy softening that exceeds expectations for EPC.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Phase excitations of stripes couple to the lattice and create a splitting of the in-phase and out-of-phase oscillation modes (35). However, the phonon anomaly is expected (35) to exist within a narrow (17,19,20). This is supported by a nonmonotonically increasing phonon intensity versus momentum and an excitation energy softening that exceeds expectations for EPC.…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, the here reported softening magnitude in LESCO is consistent with typical phononic self-energy effects ( 10 , 33 ). In addition, the intensity enhancement in the Bi-based compounds is more intense and leads to a dome-shaped h dependence ( 17 , 19 , 20 ), whereas in LESCO, the enhanced intensity is still smaller compared to that near the zone boundary ( Fig. 3D ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, as they do affect the shape of the Fermi surface via hybridization between energy bands derived from the CuO 2 planes and the CuO chains, they may thus indirectly influence the propensity of the electron system in the CuO 2 planes to CDW formation. The importance of electron-phonon interactions (EPI) for the formation of the CDW in the cuprates has been highlighted [9,26,41,[46][47][48][49], and research on classical CDW compounds has shown that its momentum dependence is also a critical parameter [50][51][52]. We argue here that the pronounced a=b anisotropies of EPI for high-energy phonons reported in YBCO [53,54] reflect the influence of the CuO chains on the EPI and play an important role in destabilizing the 3D a-CDW relative to the b-CDW.…”
mentioning
confidence: 99%